The impact of capital flight on economic development: An empirical analysis from Palestine - Badwan , Nemer (Asian Journal of Economics and Empirical Research, 2024)
This study focused on the function of capital flight to ascertain the true impact of the phenomenon of capital flight on economic development in Palestine and aimed to analyze the short- and long-term dynamic relationship between capital flight and economic development, including other affected variables. This research employed a quantitative research design and the descriptive analysis method. The analysis uses quarterly data from 2004 to 2022. This study employed the autoregressive distribution lag (ARDL) bound testing approach. Actual data from Palestine spanning the years 2004-2022 yielded significant findings. Based on heteroskedastic dynamic regression as an ARDL panel model, important findings were reached. First, both local country fundamentals and global variables have an impact on economic development and its rates over the long term, but in the near term, global forces may be predominantly recognized as drivers. Second, the variable of interest, capital flight, has a favorable impact on tax advantages. The empirical findings revealed that the short- and long-run analyses are consistent with each other. This necessitates putting into practice a variety of tactics, from creating efficient judicial and political institutions to encouraging economic development through managing macroeconomic issues. This study provides a fresh insight for policymakers to evaluate the impact of capital flight on economic development factors when coordinating fiscal and monetary policy in Palestine. The monetary and fiscal authorities should create an efficient policy framework. Palestine must reduce and stop the outflow of cash from inside its borders to improve its capacity to pay back its loans and debts to foreign creditors.